Hemolitic Anemia due to Glucose-6-Phosphate Dehydrogenase Deficiency Burdened by Cholelithiasis: Clinical Case - Olga A. Bludova; Yaroslav M. Chuyko; Luibov E. Larina (Union of pediatricians of Russia, 2023)
Background. Glucose-6-phosphate dehydrogenase deficiency is one of the most frequent enzyme defects leading to hemolysis. About 2% of Russian Federation population have this pathology. This clinical case demonstrates such complication of this disease as cholelithiasis.Clinical case description. Patient B., 17 years old, is followed up by hematologist for anemia due to glucose6-phosphate dehydrogenase deficiency. Biliary calculi were revealed in 2019. Skin and scleral icterus was noted during examination, as well as soreness in the right hypochondrium during palpation. Magnetic resonance cholangiopancreatography has shown two calculi in the distal parts of the ductus choledochus, gallstones, dilatation of the common hepatic and cystic ducts. Complete blood count: hyperchromic megalocytic anemia. Biochemical blood test: hyperbilirubinemia (mostly direct one) after 2 days of hospitalization. Endoscopic lithoextraction from ductus choledochus was performed. Drug therapy was prescribed. Positive dynamics were mentioned at control tests. The patient was discharged in a satisfactory condition on the 10th day.Conclusion. Adequate diagnosis and adequate management promote favorable disease outcome.